2016
DOI: 10.1063/1.4967309
|View full text |Cite
|
Sign up to set email alerts
|

Breaking network connectivity leads to ultralow thermal conductivities in fully dense amorphous solids

Abstract: We demonstrate a method to reduce the thermal conductivity of fully dense (above the rigidity percolation threshold) amorphous thin films below the minimum limit by systematically changing the coordination number through hydrogenation. Studying a-SiO:H, a-SiC:H, and a-Si:H thin films, we measure the thermal properties using time-domain thermoreflectance to show that thermal conductivity can be reduced below the amorphous limit by a factor of up to two. By experimentally investigating the thermophysical paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Thermal conductivity.-The out-of-plane thermal conductivity and interfacial thermal resistance between the ALD high-k dielectrics and the Si substrate was determined via TDTR measurements that have been previously described. 58,146 Briefly, an aluminum film with nominal thickness of 80 nm was first deposited on the ALD high-k dielectrics via E-beam evaporation. The samples were then exposed to a short (<1 ps) pulsed optical beam from an oscillating Ti:sapphire laser operating at a repetition rate of 80 MHz centered at a wavelength of 800 nm.…”
mentioning
confidence: 99%
“…Thermal conductivity.-The out-of-plane thermal conductivity and interfacial thermal resistance between the ALD high-k dielectrics and the Si substrate was determined via TDTR measurements that have been previously described. 58,146 Briefly, an aluminum film with nominal thickness of 80 nm was first deposited on the ALD high-k dielectrics via E-beam evaporation. The samples were then exposed to a short (<1 ps) pulsed optical beam from an oscillating Ti:sapphire laser operating at a repetition rate of 80 MHz centered at a wavelength of 800 nm.…”
mentioning
confidence: 99%
“…Later, King et al 16 illustrated that, by introducing hydrogen impurities in amorphous SiC, the connectivity between the atoms transitions from a rigid to a percolated network, resulting in a reduction of thermal conductivity by nearly an order of magnitude. In a similar study, Braun et al 17 showed that, by altering hydrogen concentration in a -SiC:H and a -SiO:H, the thermal conductivity can be suppressed by a factor of two. In all of these studies, the change in the number of bonds between constituent elements is obtained by introducing an additional impurity, such as fluorine or hydrogen, to the baseline amorphous composition.…”
Section: Introductionmentioning
confidence: 93%
“…Tuning n c has previously been shown to enable tuning of, for example, the presence of locons and hence affect the other modal types and consequently the value of κ. 36,62 Also notably, thermal conductivity has previously been shown to plateau when decreasing the network connectivity below n c = 3 for several systems as also suggested in one of the first papers on TCT by Thorpe. 63,64 Qualitatively, this would thus explain the lower slope in Figure 5B for the borate glasses compared to the other systems.…”
Section: Glass-idmentioning
confidence: 68%
“…These differences between different glass series may be explained by their differences in atomic constraints, with the alkali borate system generally featuring the lowest number of constraints per atom ( n c ∼ 3.2), while the other glass series have higher n c values. Tuning n c has previously been shown to enable tuning of, for example, the presence of locons and hence affect the other modal types and consequently the value of κ 36,62 . Also notably, thermal conductivity has previously been shown to plateau when decreasing the network connectivity below n c = 3 for several systems as also suggested in one of the first papers on TCT by Thorpe 63,64 .…”
Section: Resultsmentioning
confidence: 87%